Penentuan Rasio-Rasio Keuangan Yang Berpengaruh Terhadap Kesehatan Keuangan Perusahaan Asuransi Umum Di Indonesia - Martini, Andi Indra (Movere Journal, 2019)
The purpose of this research is to determine financial ratios that affected financial appropriateness for the general insurance firms in Indonesia. The research is undertaken in Jakarta at Indonesian General Insurance Association office (AAUI). This research used survey method in collecting financial data of General Insurance Firms in Indonesia. All collected data in this research is originally taken from financial reports published by the Indonesian Insurance Board (DAI), called Indonesian Insurance, data was published in 1999 to 2003. Methods of analyses used in this research are financial ratios and discrimant analysis. The discriminant analysis is processed through SPSS version 12. The results indicated that there was a significant difference between well financial performances of general insurance firms and inappropriate financial performances of general insurance firms. These can be seen at F test, Sig and Wilk’s Lambda. This research also could produced Z Score Model, in which could differentiate the well financial performances and inappropriate financial performances with the level of accuracy of 88%. This research discovered that the ratio that could affect the well financial performances for general insurance firms in Indonesia, are ratios between Net retention premium and equity and ratio between profit (loss) after tax to average equity. This research also shown that the government policy on Finance Minister Decision No.424/KMK 06/2003 and the plan provided on Indonesian Insurance Architect, would be able to improve financial performances of general insurance firms.